Evidence for Reverse Causality in the Association Between Blood Pressure and Cardiovascular Risk in Patients With Chronic Kidney Disease. Issue 2 (February 2017) - Herrington, William; Staplin, Natalie; Judge, Parminder K.; Mafham, Marion; Emberson, Jonathan; Haynes, Richard; Wheeler, David C.; Walker, Robert; Tomson, Charlie; Agodoa, Larry; Wiecek, Andrzej; Lewington, Sarah; et al.
Abstract : Among those with moderate-to-advanced chronic kidney disease, the relationship between blood pressure (BP) and cardiovascular disease seems U shaped but is loglinear in apparently healthy adults. The SHARP (Study of Heart and Renal Protection) randomized 9270 patients with chronic kidney disease to ezetimibe/simvastatin versus matching placebo and measured BP at each follow-up visit. Cox regression was used to assess the association between BP and risk of cardiovascular disease among (1) those with a self-reported history of cardiovascular disease and (2) those with no such history and, based on plasma troponin-I concentration, a low probability of subclinical cardiac disease. A total of 8666 participants had a valid baseline BP and troponin-I measurement, and 2188 had at least 1 cardiovascular event during follow-up. After adjustment for relevant confounders, the association between systolic BP and cardiovascular events was U shaped, but among participants without evidence of previous cardiovascular disease, there was a positive loglinear association throughout the range of values studied. Among those with the lowest probability of subclinical cardiac disease, each 10 mm Hg higher systolic BP corresponded to a 27% increased risk of cardiovascular disease (hazard ratio, 1.27; 95% confidence interval, 1.11–1.44). In contrast, the relationship between diastolic BP and cardiovascular risk remained U shaped irrespective of cardiovascular disease history or risk of subclinical disease. In conclusion, the lack of a clear association between systolic BP and cardiovascular risk in this population seems attributable to confounding, suggesting that more intensive systolic BP reduction may be beneficial in such patients. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00125593. Abstract : Supplemental Digital Content is available in the text.